Analisis Implementasi Bagi Hasil Pada Simpanan Akad Mudharabah dalam Tinjauan Fiqh Muamalah: (Studi Kasus Di BMT Amanah Ummah Cabang Jambangan Surabaya) - Qoyyimah; Uswatun Chasanah (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2022)
This research has the aim of knowing that the implementation of Profit Sharing at BMT Amanah Ummah Jambangan Surabaya Branch on Mudharabah contract savings is appropriate in terms of Muamalah Fiqh. This research is field research, namely by collecting data obtained directly from the field. This method is a descriptive qualitative method, with data sources from observations, direct interviews and documentation. And data analysis uses data reduction, data presentation, then drawing conclusions. The result is, BMT Amanah Ummah Jambangan Surabaya Branch has set a profit sharing ratio of 20% of real profits for Shahibul Maal and 80% for Mudharib. These provisions have been determined by BMT, then agreed between both parties. Muamalah Fiqh review regarding the implementation of this profit sharing, in terms of harmony and the terms of cooperation according to Jumhur Ulama have been fulfilled. Also from a legal perspective, the fulfillment of the pillars and conditions of Mudharabah have been fulfilled.